2020
DOI: 10.1590/2177-6709.25.1.028-035.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yd:YAG laser irradiation on the shear bond strength of orthodontic metal brackets

Abstract: Objective: The purpose of this study was to evaluate the effect of the Yd:YAG laser irradiation on orthodontic bracket base surface. Shear bond strength (SBS) values and sites of the bonding failure interfaces were quantified. Methods: Brackets were divided into two groups: OP (One Piece - integral sandblast base) and OPL (One Piece - laser irradiation). The brackets were randomly bonded on an intact enamel surface of 40 bovine incisors. The SBS tests were carry out using a universal test machine. A stereomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The attachments with larger apertures show better air displacement from the surface and better resin penetration into the spaces, resulting in higher bond strengths [ 14 , 20 ]. Although several studies have reported that fine mesh gauges due to larger apertures demonstrate higher bond strength, some studies have indicated no significant differences between various mesh gauges [ 8 , 13 , 16 , 24 , 26 – 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The attachments with larger apertures show better air displacement from the surface and better resin penetration into the spaces, resulting in higher bond strengths [ 14 , 20 ]. Although several studies have reported that fine mesh gauges due to larger apertures demonstrate higher bond strength, some studies have indicated no significant differences between various mesh gauges [ 8 , 13 , 16 , 24 , 26 – 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore it seems that laser etching of the bonding surface can improve the bond strength of other ABS designs [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations